Rorty on Hermeneutical Injustice, Liberal Redescription and Utopian Imagination - Penelas, Federico (ENDOXA, 2019)
My purpose is to use Miranda Frickers’ concepts of testimonial injustice and hermeneutical injustice to draw a distinction between the policy of tolerance and the policy of solidarity in Rortyan liberalism. I shall focus on the policy of solidarity interpreted as unfolding in two phases of the imagination: the phase of critical imagination and that of utopian imagination. I advocate that critical imagination may be understood as focusing on overcoming hermeneutical injustice through what I term liberal redescription. Lastly, I critique the Rortyan project on what I view as an inadequate inclination to restrict critical imagination on the basis of adopting a criterion that focuses on flaws in the development of utopian imagination.